Study on culture of stable aerobic granular sludge - Xu Yujie; Chen Shuo; Wu Chuanqi; Zhang Zhiming (E3S Web of Conferences, 2024)
In this study, three reactors were established with anaerobic plug-flow times of 1.5 hours, 1 hour, and 0.5 hours. The results indicated that the anaerobic plug-flow time of 1 hour constructed favorable "feast- famine" period ratio, promoting the enrichment of microorganisms that stored and utilized the internal carbon source, such as Phosphate and Glycogen Accumulating Organisms (PAO and GAO). This resulted in the formation of granular sludge with both short granulation time and structural stability. In contrast, shortening the anaerobic feed time to 0.5 hours was detrimental to the growth of GAO, leading to slow granularization of aerobic sludge. The anaerobic influent time of 1.5 h leads to the shortening of starvation period and poor stability of particle structure.